Human amnion epithelial cells and their soluble factors reduce liver fibrosis in murine non‐alcoholic steatohepatitis. Issue 8 (2nd April 2019) - Kuk, Nathan; Hodge, Alexander; Sun, Ying; Correia, Jeanne; Alhomrani, Majid; Samuel, Chrishan; Moore, Gregory; Lim, Rebecca; Sievert, William
Abstract: Background and Aim: Non‐alcoholic steatohepatitis (NASH) can lead to cirrhosis and hepatocellular carcinoma. Currently, lifestyle modification is the only effective treatment. We have shown that human amnion epithelial cells (hAECs) reduce inflammation and fibrosis in toxin‐induced liver injury models. We examined the effect of these cells and the soluble factors released by the cells into culture medium (hAEC conditioned medium [hAEC‐CM]) in a diet‐induced murine NASH model. Methods: C57BL/6J male mice received a Western "fast food diet" for 42 weeks. Group 1 received an intraperitoneal injection of 2 × 10 6 hAECs at week 34, group 2 received an additional hAEC dose at week 38, and group 3 received thrice weekly hAEC‐CM injections intraperitoneal for 8 weeks from week 34. Liver fibrosis area, inflammation, and fibrosis regulators were measured by immunohistochemistry, qPCR, and gelatin zymography. Metabolic parameters were also assessed. Results: Fast food diet‐fed mice demonstrated peri‐cellular hepatic fibrosis, inflammation, and steatosis typical of NASH. Liver fibrosis area was reduced by 40% in hAEC‐treated and hAEC‐CM‐treated mice. hAEC treatment significantly reduced pSMAD 2/3 signaling and the number of activated hepatic stellate cells and liver macrophages. Matrix metalloproteinase 2 and 9 gene and protein expression were variably affected. hAEC treatment did not alter the NASH activity score or metabolic parameters such as bodyweight, total cholesterol, or glucose tolerance. Conclusion: Human amnion epithelial cell and hAEC‐CM significantly reduced hepatic inflammation and fibrosis in a diet‐induced non‐alcoholic fatty liver disease model. Although hAEC and hAEC‐CM did not affect the metabolic components of NASH, their therapeutic potential is promising and warrants further investigation.